Development of Learning Media with Mathematical Understanding in Geometric Sequences and Series within Malay Islamic Context - Amaliah, Suci; Syutaridho; Ramury, Feli; Fitrianti, Yuli (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2023)
This research aims to develop mathematical learning materials for understanding geometric sequences and series within the context of Malay Islamic culture, which can provide a valid and practical connection to mathematics and enhance mathematical comprehension skills. The research follows the Tessmer 1993 research procedure, encompassing two stages: introduction and prototyping, with a formative evaluation process. The research findings indicate that the learning materials are suitable for implementation, as demonstrated by assessments. The validity of the materials, as assessed by experts, is 93%, signifying their high suitability. The practicality of the learning materials, based on student feedback, is 79%, indicating their practical utility. As for their potential to enhance mathematical abilities, the results show an 82% positive impact on mathematical understanding abilities, as determined from student practice. Furthermore, the mathematical understanding ability of students using these learning materials was rated at 75%, indicating a high level of comprehension of geometric sequence and series content. Consequently, the developed learning materials are suitable for use in the educational process. DOI: https://doi.org/10.22342/jpm.17.3.21971.379-396